Preparation and Evaluation of Mouth Dissolving Tablet of Albendazole Using Different Concentrations of Super-Disintegrant - Bavaskar, Kedar Rupa; Pote, Supriya; Vidhate, Prasad; Patil, Vinit; Jain, Ashish (Journal of Fundamental and Applied Pharmaceutical Science, 2024)
Anthelmintic medications are anticipated to act more quickly and have greater absorption. Mouth-dissolving albendazole tablets were created using a direct compression approach and a mixture of super disintegrants to accomplish rapid disintegration of the tablets in the oral cavity. The preparation of ten batches of mouth-dissolving tablets using different grades of Kollidon, crospovidone, sodium starch glycolate, and croscarmellose sodium as super disintegrants produced the greatest results. For a compatibility investigation, FTIR was used to characterize the drug and physical mixture. An optimization technique was used to forecast the most effective formulation out of all the prepared combinations. All the physical characteristics of the tablet are within the limit. All preformulation results indicated good flow properties. Disintegration time and drug content of the F4 batch were found to be 28 seconds and 95.69%, respectively. In vitro release of the drug was performed in a phosphorus buffer pH 6.8 for 40 min, in which F4 shows maximum drug release. Based on the stability studies, it was confirmed that the optimized formulation remained at accelerated stability conditions. It was discovered that the mouth-dissolving tablet exhibits effective drug release.